2020
DOI: 10.1101/2020.01.06.894287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analysis of human embryos reveals diverse patterns of aneuploidy and mosaicism

Abstract: Less than half of human zygotes survive to live birth, primarily due to aneuploidies of meiotic or mitotic origin. Mitotic errors lead to chromosomal mosaicism, defined by multiple cell lineages with distinct chromosome complements. The incidence and fitness consequences of chromosomal mosaicism in human embryos remain controversial, with most previous studies based on bulk DNA assays or comparisons of multiple biopsies of a few embryonic cells. Single-cell genomic data provide an opportunity to quantify mosai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Low-level mosaicism is a common feature of early human development. A recently published study on single-cell genomic data revealed widespread mosaic aneuploidies, with 80% embryos harboring at least one putative aneuploid cell, with no significant enrichment of aneuploid cells in the TE compared to the ICM [31]. These observations conclusively demonstrate that mosaicism in blastocyst-stage embryos is basically a normal physiological phenomenon that can be found in almost all embryos [14,31].…”
Section: Discussionmentioning
confidence: 52%
“…Low-level mosaicism is a common feature of early human development. A recently published study on single-cell genomic data revealed widespread mosaic aneuploidies, with 80% embryos harboring at least one putative aneuploid cell, with no significant enrichment of aneuploid cells in the TE compared to the ICM [31]. These observations conclusively demonstrate that mosaicism in blastocyst-stage embryos is basically a normal physiological phenomenon that can be found in almost all embryos [14,31].…”
Section: Discussionmentioning
confidence: 52%
“…few cells and cellular fragmentation indicative of cell death) ( Minasi et al, 2016 ; Fragouli et al, 2013 ). Moreover, despite forming morphologically normal blastocysts, aneuploid embryos display transcriptional and epigenetic alternations that may compromise their subsequent development ( McCallie et al, 2016 ; Licciardi et al, 2018 ; Starostik et al, 2020 ). Autosomal monosomies typically lead to biochemical losses, whereas autosomal trisomies are associated with silent miscarriage (presence of extra-embryonic membranes but lack of embryonic structures) and first-trimester miscarriage ( Ljunger et al, 2005 ; Martinez et al, 2010 ; Ferro et al, 2003 ; Stephenson et al, 2002 ).…”
Section: When Things Go Wrong: Aneuploidy and Pregnancy Lossmentioning
confidence: 99%
“…Autosomal monosomies typically lead to biochemical losses, whereas autosomal trisomies are associated with silent miscarriage (presence of extra-embryonic membranes but lack of embryonic structures) and first-trimester miscarriage ( Ljunger et al, 2005 ; Martinez et al, 2010 ; Ferro et al, 2003 ; Stephenson et al, 2002 ). In addition, alterations in the number of chromosomes can be a consequence of mitotic alterations during the first three cleavage divisions, which lead to the formation of mosaic human embryos ( Popovic et al, 2019 ; Starostik et al, 2020 ; Mantikou et al, 2012 ). Given the inaccessibility of human embryos at these stages, several fundamental questions remain to be addressed.…”
Section: When Things Go Wrong: Aneuploidy and Pregnancy Lossmentioning
confidence: 99%
“…With the recent adoption of single-cell GW haplotyping methods in PGT, the existence of androgenetic, gynogenetic and triploid profiles in human blastomere and trophectoderm biopsies has been uncovered (49,(93)(94)(95)(96). Moreover, mixoploidy and/or chimerism was recently inferred from single-cell transcriptome data in human blastocysts (97). Here, we directly show GW aberrations, identified in biopsied cleavage-stage embryos, to persist throughout the preimplantation period forming mixoploid and/ or chimeric human blastocysts.…”
Section: Mixoploidy and Chimerism Occur In Humanmentioning
confidence: 55%